Vilcabamba and the Archaeology of Inca Resistance - Bauer, Brian S.; Fonseca Santa Cruz, Javier; Aráoz Silva, Miriam (Los Angeles : Cotsen Institute of Archaeology Press, 2015)
"The sites of Vitcos and Espíritu Pampa are two of the most important Inca cities within the remote Vilcabamba region of Peru. The province has gained notoriety among historians, archaeologists and other students of the Inca, since it was from here that the last independent Incas waged a nearly forty year-long war (AD 1536-1572) against Spanish control of the Andes. Building on three years of excavation and two years of archival work, the authors discuss the events that took place in this area, speaking to the complex relationships that existed between the Europeans and Andeans during the decades that Vilcabamba was the final stronghold of the Inca empire. This has long been a topic of interest for the public; the results of the first large scale, scientific research conducted in the region will be illuminating for scholars as well as for general readers who are enthusiasts of this period of history and archaeology"--Provided by publisher.
Preface / by Brian S. Bauer -- Chronology -- An introduction to Vilcabamba / by Brian S. Bauer -- The late pre-Hispanic settlement patterns in the Vitcos region and the excavation results at the Kallanka and the double structure / by Brian S. Bauer and Miriam Aráoz Silva -- The shrine complex of Yurak Rumi / by Brian S. Bauer and Miriam Aráoz Silva -- An introduction to the city of Vilcabamba / by Brian S. Bauer -- Excavations at Tendi Pampa (Espiritu Pampa) in 2008 and 2009 / by Javier Fonseca Santa Cruz and Brian S. Bauer -- Excavations in the new sector and elsewhere at the site of Espiritu Pampa in 2008 and 2009 / by Javier Fonseca Santa Cruz and Brian S. Bauer -- Excavations at Espiritu Pampa in 2010 / by Brian S. Bauer and Miriam Aráoz Silva -- Appendix 1: The results of radio carbon tests run on charcoal recovered in Inca buildings.
JSTOR
Keywords: Incas -- Peru -- Vilcabamba Mountains -- Antiquities; Excavations (Archaeology) -- Peru -- Vilcabamba Mountains; Vilcabamba Mountains (Peru) -- Antiquities; Incas -- Peru; Vilcabamba Mountains (Peru) -- History, Military -- 16th century; Vilcabamba Mountains (Peru) -- Ethnic relations -- History -- 16th century; Incas -- Pérou -- Vilcabamba, Cordillère de -- Antiquités.; Fouilles (Archéologie) -- Pérou -- Vilcabamba, Cordillère de; Incas -- Pérou.; Vilcabamba, Cordillère de (Pérou) -- Histoire militaire -- 16e siècle.; Vilcabamba, Cordillère de (Pérou) -- Relations interethniques -- Histoire -- 16e siècle.; SOCIAL SCIENCE; Antiquities; Ethnic relations; Excavations (Archaeology); Incas; Incas -- Antiquities; Peru; Peru -- Vilcabamba Mountains; 1500-1599; Electronic books; History; Military history